Representasi Iklan Ramai Sepi Bersama Versi #silaturahmisetiaphari - Muhammad Ruslan Ramli; Asma Rokhmatuddhuha; Ikbal Rachmat; Ivanina Zuhdi (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2022)
AbstractThis study discusses Eid Mubaraq-themed advertisements which published in social media. During the Covid-19 pandemic, the people can't go anywhere, including on the day of Eid Mubaraq. Everyone is asked to stay at home to avoid the spread of Covid-19. This research aims to reveal the advertising message of